Benefits for Companies by Hiring Workers with Disabilities - Emaliana, Ive; Manuaba, Ida Bagus Surya; W., Agustina Shinta Hartati (Indonesian Journal of Disability Studies, 2022)
Workers with disabilities are still minimally absorbed in the job market in the formal sector. Even though there are several benefits that the company gets when it employs workers with disabilities. This study uses the library study method and interviews with 2 people with disabilities of which 1 works in the formal sector and 1 works in the informal sector. Although the Law on Persons with Disabilities has set a minimum quota for disabled workers in companies, its implementation has not been in line with expectations. Whereas companies that employ workers with disabilities will get benefits such as a good corporate image because they employ workers with disabilities, create an inclusive work environment.